please solve & help
Attachments:
![](https://hi-static.z-dn.net/files/d9e/8b9933e37b207e4aec89e32f3b831d67.jpg)
Answers
Answered by
0
Answer: ITS VERY SHORT I CANT READ IT PLEASE GIVE A ZOOMED PHOTO
Step-by-step explanation:
Answered by
0
Answer:
sum of (-20) +(-36)+(-234)
= -20-36-234
= -56-234
= -290
sum of (-196)+(-69)+1004
= -196-69+1004
= -265+1004
= 739
therefore, -290-739
= -449 ans
HOPE IT HELPS U( ^ ^ )
Similar questions
English,
5 months ago
Science,
5 months ago
English,
5 months ago
Science,
11 months ago
Computer Science,
11 months ago
English,
1 year ago
Psychology,
1 year ago